Dysexecutive symptoms among a non-clinical sample: a study with the use of the Dysexecutive Questionnaire. - Chan, Raymond C. K. (British Journal of Psychology, 2001)
Clinical studies indicate that damage to the frontal lobes may lead to a set of symptoms collectively known as ‘Dysexecutive syndrome’, which is characterized by changes in emotion, personality, motivation, behaviour and cognitive aspects. Factor analytical study using questionnaires measuring dysexecutive problems in everyday life also suggests a fractionation of the dysexecutive syndrome among patients with neurological disorders. As yet, very little research has been conducted to explore the base-rate of executive problems in everyday life among the non-clinical population. This pilot study aimed to explore dysexecutive behaviour similar to that of dysexecutive syndrome reported by a non-clinical sample. A total of 93 presumably normal participants were recruited. The Dysexecutive Questionnaire and a set of clinical tests of executive function were administered to all participants. A 5-factor solution very similar to that of a previous study was derived: inhibition (factor 1), intentionality (factor 2), knowing–doing dissociation (factor 3), in-resistance (factor 4), and social regulation (factor 5). Correlation was established among the derived factors and tests of executive function. This study provides empirical evidence that a non-clinical sample may encounter similar dysexecutive behaviours in daily life. The issue of the fractionation of the executive system among the non- clinical sample will also be discussed. Reprinted by permission of the publisher.